Development of international entrepreneurship based on corporate accounting and reporting According to IFRS : part A - Abdurakhmanova, Gulnora K.; Burkhanov, Aktam U.; Abdusalomova, Nodira B.; Ergasheva, Shakhlo T. (Advanced series in management series ;, 2024)
Development of International Entrepreneurship based on Corporate Accounting and Reporting According to IFRS: Part A delves into the role of corporate accounting and reporting under IFRS in advancing international business management, proposing recommendations to bolster this role in fostering cross-border trade in today's era of adaptable global partnerships. The volume first establishes the theoretical framework for IFRS, and then explores its managerial implications in international business. The central argument posits IFRS as pivotal for entrepreneurial strategic management, particularly in light of globalization's organizational shifts and the rise of the Fourth Industrial Revolution and the digital economy. Aimed at scholars of IFRS development and application, Development of International Entrepreneurship based on Corporate Accounting and Reporting According to IFRS: Part A offers advanced theoretical and methodological insights for tailoring IFRS to evolving needs in global trade partnerships, alongside guidance for effectively integrating IFRS into the management practices of international enterprises.